2019
DOI: 10.1186/s13019-019-0891-1
|View full text |Cite
|
Sign up to set email alerts
|

Failed MitraClip therapy: surgical revision in high-risk patients

Abstract: Background MitraClip implantation is a valid interventional option that offers acceptable short-term results. Surgery after failed MitraClip procedures remains challenging in high-risk patients. The data on these cases are limited by the small sample numbers. Aim The aim of our study is to show, that mitral valve surgery could be possible and more advantageous, even in high-risk patients. Methods Between 2010 and 2016, nine patients underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
(29 reference statements)
2
14
0
Order By: Relevance
“…The main finding of this study is the feasibility of mitral valve surgery in a highest risk patient cohort with a predominantly complex constellation of mixed degenerative/functional MR and significantly reduced left ventricular ejection fraction who were initially classified as high surgical risk and, therefore, inoperable (Table 2). Our results are in line with recent publications on post‐MC surgical bailout, in which feasibility of surgery with acceptable results were equally demonstrated 9,10 . Organ failure resulting from cardiogenic shock/sepsis as possible risk factor for perioperative mortality in our case and in the patient‐cohort recently presented by Takayuki et al 10 calls for close meshed monitoring of these patients and timely surgery if indicated and feasible.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The main finding of this study is the feasibility of mitral valve surgery in a highest risk patient cohort with a predominantly complex constellation of mixed degenerative/functional MR and significantly reduced left ventricular ejection fraction who were initially classified as high surgical risk and, therefore, inoperable (Table 2). Our results are in line with recent publications on post‐MC surgical bailout, in which feasibility of surgery with acceptable results were equally demonstrated 9,10 . Organ failure resulting from cardiogenic shock/sepsis as possible risk factor for perioperative mortality in our case and in the patient‐cohort recently presented by Takayuki et al 10 calls for close meshed monitoring of these patients and timely surgery if indicated and feasible.…”
Section: Discussionsupporting
confidence: 91%
“…This approach is supported by the fact that the overall impact of MC in secondary MR is yet to be irrevocably established 8 . Publications dealing with persistent or recurrent MR after MC intervention and subsequent management strategies in this often times difficult situation are increasing and need to be evaluated to better understand the future perspectives of catheter‐based MV intervention 9,10 . Factors guiding the decision as to whether to treat a case of failed MC intervention conservatively, catheter‐based or surgically is yet to be fully established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical intervention either by repairing or replacing the MV will stand as an option in such situation alternative to the repeated clipping, especially in situations with acute failure, like leaflets detachment, or severe uncontrollable MR caused by leaflet perforation, in addition to hemodynamic compromise. 6 Studies evaluating reinterventions after MitraClip are scarce, and the management plan for this particular patient category is not well-established. In this study, we aimed to report our experience in reinterventions after MitraClip procedures and describe the outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical intervention either by repairing or replacing the MV will stand as an option in such situation alternative to the repeated clipping, especially in situations with acute failure, like leaflets detachment, or severe uncontrollable MR caused by leaflet perforation, in addition to hemodynamic compromise 6 …”
Section: Introductionmentioning
confidence: 99%